Decreasing costs of renewables: Insights on energy sector planning and climate policy from three country case studies - Johannes Eckstein; Marie-Jeanne Kurdziel; Leonardo Nascimento Castro; Jose Antonio Ordonez (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2020)
This study builds on three case studies in Argentina, Indonesia and Mexico which analyse the implications of falling costs for renewable energy systems on the countries' energy sector planning and climate policy. Each case study consists of two country specific reports. The first report analyses how falling costs of renewable energy could impact country specific power sector development. The second report analyses the process of climate and renewable energy target setting, as well as the prevalent narrative around renewable energy integration. Finally, the present report provides a cross-country synthesis of all case studies, providing insights into the question of how falling costs of renewable energy systems might support the achievement of the goals of the Paris Agreement. Globally falling cost figures for solar PV and wind energy do not naturally translate into increased ambition in planning. The integration of these technologies to the energy system still face substantial barriers in our case study countries: The integration of higher shares of renewable energy goes along with investments into transmission and distribution network modernisation, network expansion and interconnections between power grids. Though an important element, falling costs for renewable energy projects alone do not necessarily translate into overall reduced power system costs. While globally falling costs for wind and solar PV are indicative for learning curve effects in the manufacturing of these technologies, the LCOE of renewable projects is highly sensitive to financing costs. These are largely determined by the local political and regulatory framework and remain high in our case countries, representing a barrier. We find that a number of regulatory and administrative barriers hinder higher integration of solar PV and wind. Frequently changing regulations and ill-designed support schemes often prevail over welldesigned renewable energy auction schemes that are followed over several years. We find the political economy fossil fuels to be pivotal in the energy sector and climate planning and target setting processes. Fossil fuel endowments and a long history of natural resource exploitation lead to strong vested interests towards sustaining the use of fossil fuels to satisfy a growing electricity demand. [...]
urn:nbn:de:0011-n-6156283
Keywords: 330